1987
DOI: 10.1185/03007998709108967
|View full text |Cite
|
Sign up to set email alerts
|

The antihypertensive efficacy of nifedipine alone and in combination in general practice

Abstract: A multi-centre study in general practice involving 3242 hypertensive patients, aged up to 70 years, was carried out to evaluate the efficacy and tolerability of nifedipine used alone or in combination with other antihypertensive agents in step-care treatment. Patients were treated for up to 8 weeks with one of four regimens: nifedipine monotherapy; diuretic and nifedipine; beta-blocker plus nifedipine; and nifedipine added to a combination of diuretic and beta-blocker. All patients received 20 mg nifedipine, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…The frequency of adverse experiences in this study (32.8%) was similar to that presented by Ziegler and Bach (1986) and Duffy and Macdonald (1987), who reported 'about one-third' and a peak value of 22%, respectively. In common with pre-Drug Invest.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The frequency of adverse experiences in this study (32.8%) was similar to that presented by Ziegler and Bach (1986) and Duffy and Macdonald (1987), who reported 'about one-third' and a peak value of 22%, respectively. In common with pre-Drug Invest.…”
Section: Discussionsupporting
confidence: 90%
“…The results presented confirm the findings of 2 other reports in which nifedipine 20mg prolonged action tablet was also studied in populations of over 1000 patients in general practice settings in Switzerland (Ziegler & Bach 1986) and the UK (Duffy & Macdonald 1987). The reduction in sitting blood pressure in our programme was 25/l7mm Hg, compared with 27/ 17mm Hg (Ziegler & Bach 1986) and 29/18mm Hg (Duffy & Macdonald 1987) after the same period of 8 weeks.…”
Section: Discussionsupporting
confidence: 88%
“…The antihypertensive efficacy of the slow calcium channel blocker nifedipine has been well documented in recent years (MacGregor et al 1982(MacGregor et al , 1983Schnapp et a1 1987). Controlled clinical studies have shown that nifedipine is well suited for use by itself as well as in combination with fi-adrenoceptor blockers or diuretics (Duffy & MacDonald 1987). Its usefulness in combination with diuretics, however, is not very clear.…”
mentioning
confidence: 99%
“…Acute administration of nifedipine to normotensive and hypertensive subjects produces increased renal blood flow (Yokoyama & Kaburagi 1983), natriuresis and diuresis (Leonetti et al 1982;Schnapp 1989), but the mechanisms of nifedipine-induced natriuresis are incompletely understood and d o not show any relationship to fall in systemic blood pressure (Schnapp 1989). Short or long term use of nifedipine is associated with a moderate increase in plasma renin activity and will also promote the development of peripheral oedema which is sometimes severe and resistant t o diuretic therapy (Aoki et a1 1978;Guazzi et al 1983;Duffy & MacDonald 1987). Experimental studies showed nifedipine to cause overt urine and electrolyte retention in saline-loaded rats (Barret et al 1988).…”
mentioning
confidence: 99%